The implications of comprehensive and incremental approaches to public sector reform for the creation of a developmental state in South Africa: Case study of the Oceans Economy Operation Phakisa - Pretorius, Pieter (Graduate School of Development Policy and Practice, 2019)
In 1994, the first democratically elected government in South Africa faced the significant task of shaping new institutions and delivery transmission mechanisms capable of developing and implementing policies aimed at inclusive socio-economic growth and development. Evidence shows that the South African public sector is generally not yet able to be a key driver of development, at least not to the extent required to reduce poverty and inequality to the levels envisioned in the National Development Plan. The study argues that comprehensive public sector reform based on the principles of New Public Management was inappropriate given the unique South African political and institutional context and that incremental approaches to development are more likely to achieve results. This leaves room for the emergence of islands of effectiveness where public entrepreneurs or multi-stakeholder governed arrangements could be employed as alternative or complementary delivery transmission mechanisms. Operation Phakisa, an adaptation of the Malaysian Big Fast Results methodology, introduced a radical new approach to improving government impact. The Operation Phakisa methodology made certain assumptions about (or perhaps deliberately ignored) prevailing principal-agent relationships in South Africa and the readiness of these relationships to be challenged and transformed. Through the development and application of an analytical framework, the study examines the role of islands of effectiveness (using the Oceans Economy Operation Phakisa as a case study) as possible alternative or complementary delivery transmission mechanisms. While the Oceans Economy Operation Phakisa did not create sufficient scope for multi-stakeholder governance arrangements, some initiatives, most notably the Oil and Gas initiative, did benefit from public entrepreneurs that were able to navigate complex political and institutional realities to achieve results. Based on the outcome of the analysis, the study concludes with recommendations that could enhance the effectiveness of future iterations of Operation Phakisa.